Magnetotransport studies of two-dimensional magnetism in van der Waals materials - Ye, Chen (Nanyang Technological University, 2022)
From ancient compass to modern spintronics, magnetism has had a pivotal role in fundamental research and technological advance for millennia. To fulfill the exploded information introduced by the rapid development of artificial intelligence, extensive efforts have been paid to reduce the dimensionality of magnetic materials. The discovery of two-dimensional (2D) magnetism in van der Waals (vdW) materials, where each atomic layer vertically stacks and experiences vdW interaction, enables the long-range magnetic ordering to emerge at the monolayer limit. Exotic magnetotransport phenomena with great sensitivity toward varying parameters in the magnetic vdW materials provide unique insights into 2D magnetism. The universal compatibility to dissimilar materials without lattice-matching constraints also enables the interplay between 2D magnetism with other physical properties. This can be leveraged to the highly demanded electronic and spintronic devices with miniaturized circuits and ultimate performance. Hence, my research focuses on magnetotransport studies of 2D magnetic vdW materials to reveal the novel phenomena in reduced dimensions and the underlying mechanism. The investigation is composed of three parts, namely (i) searching for new candidates to enrich the 2D magnetic family, (ii) revealing the magnetic order governed by fundamental physics, and (iii) investigating the interplay of magnetism and topology.